Publication of a Quality Content as a Tool for Strengthening Consumer Trust in the Modern Business World - Octaviani, Ghina Faidah; Rijkiah, Jian; Magdalena, Sherly; Sianturi, Risbon (Universitas Pendidikan Indonesia, 2025)
This article discusses how digital platforms and content creators play a vital role in the success of growing businesses, especially in the culinary sector. By utilizing social media, small businesses can strengthen their branding and build consumer trust through quality and relevant content. A case study of a successful culinary entrepreneur shows that consistent and innovative branding strategies significantly contribute to business growth in a competitive market. This study uses a qualitative approach with data collection methods in the form of observation and in-depth interviews. The research findings emphasize the importance of collaboration between entrepreneurs and content creators in building a strong brand, attracting customers, and forming a loyal community. In addition, this article provides practical strategies that can be applied by aspiring entrepreneurs, especially the younger generation, in starting a digital-based business. By utilizing digital technology and creative ideas, entrepreneurs can create new job opportunities and contribute to the advancement of the local economy.